394 MELANOMA-ASSOCIATED ONCOGENE MICROPHTHALMIA-ASSOCIATED TRANSCRIPTION FACTOR IS UP-REGULATED BY ALTERTIONS IN MICRO-RNA. Issue 1 (1st January 2007) - Coffey, D.; Bemis, L.; Erickson, P.; Robinson, S.; Classen, E.; Robinson, W.
Abstract : Microphthalmia-associated transcription factor (MITF) is an antiapoptotic protein amplified in melanoma cell lines, and its overexpression is correlated with a decreased survival in patients with malignant melanoma. A bioinformatics-based approach predicts micro-RNA-137 as a regulator of MITF. Micro-RNA (miRNA) is a recently discovered class of noncoding RNA that negatively regulates gene expression. Mutations in miRNA or in their target binding site have been implicated in tumorigenesis. We hypothesized that alterations in the function of miRNA-137 may be responsible for MITF overexpression in melanoma. We directly sequenced the DNA region encoding miRNA-137 in samples obtained from patients with melanoma and controls. We identified a 15-nucleotide variable number tandem repeat (VNTR) within the primary miRNA-137 sequence near the critical Drosha-DGCR8 binding site. We found that patients with melanoma had a greater number of repeats compared with controls. To investigate if the presumed wild-type miRNA-137 with the fewer number of VNTRs regulates MITF, we transfected the wild-type primary miRNA-137 gene into human melanoma cell lines and measured MITF expression by Western blot. Our preliminary data suggest that cells transfected with wild-type miRNA-137 have decreased MITF expression compared with vector control. These data suggest that wild-type miRNA-137 is capable of regulating MITF. Future experiments are being performed to determine if the miRNA-137 with the greater number of VNTRs leads to overexpression of MITF and contributes to the development and progression of melanoma.